QARAQALPAQ JAZBA ÁDEBIYATÍNDA DÁSTAN JANRÍNÍŃ RAWAJLANÍWÍ - Ganieva, G.M. (SCIENCE and SOCIETY, 2025)
This article provides a general overview of the epic genre, discussing the uniqueness of early epics, their place in literature, and the skill of creating characters. At the same time, the genre and artistic features of epics in 20th-century Karakalpak literature, the skill of writers in creating the image of heroes, were discussed.